Distributional equity as a consideration in economic and modelling evaluations of health taxes: A systematic review. Issue 9 (September 2020) - Jain, Vageesh; Crosby, Liam; Baker, Peter; Chalkidou, Kalipso
Highlights: Evidence on health taxes did not routinely consider distributional impact. Alcohol tax evaluations were particularly weak in considering distributional impact by income-group. Where considered, tobacco taxes were found to disproportionately benefit lower-income groups. The impact of a sugar-sweetened-beverage (SSB) tax varied across study population income-groups. Abstract: Purpose/setting: The extent to which distributional equity is incorporated into evaluations of the (potential or observed) impact of health taxes is unclear. This systematic review of economic and modelling evaluations investigating taxation on tobacco, sugar-sweetened-beverages (SSBs), or alcohol aims to assess the proportion that have considered distributional impact by income or socioeconomic group. Secondary aims included summarising the reported distributional impacts, for both costs and health benefits. Findings: Of 4656 search results, 69 studies were included. The majority were economic analyses with epidemiological modelling, with studies on SSB taxes being of the highest quality. Tobacco was most commonly investigated tax, with 37 evaluations. Of these, 12 (32 %) considered distributional equity, with six (27 %) of 22 included SSB evaluations doing the same, and none for alcohol. A tobacco tax favoured lowerincome groups in the distribution of costs in all identified evaluations and for health benefits in nine out of 12 evaluations (75 %). For SSBs, four evaluations (67 %) found costs to favour low-income groups, with three (50 %) for health benefits. Conclusions: Despite recommendations, evaluations of health taxes do not routinely consider the distributional impact of both costs and health benefits. Evaluations for alcohol taxation are particularly weak in this regard. Where investigated, the majority of evidence found tobacco taxation to favour low-income groups, whereas the limited evidence for SSBs is mixed.